2015
DOI: 10.1002/2014ja020761
|View full text |Cite
|
Sign up to set email alerts
|

Fast damping of ultralow frequency waves excited by interplanetary shocks in the magnetosphere

Abstract: Analysis of Cluster spacecraft data shows that intense ultralow frequency (ULF) waves in the inner magnetosphere can be excited by the impact of interplanetary shocks and solar wind dynamic pressure variations. The observations reveal that such waves can be damped away rapidly in a few tens of minutes. Here we examine mechanisms of ULF wave damping for two interplanetary shocks observed by Cluster on 7 November 2004 and 30 August 2001. The mechanisms considered are ionospheric joule heating, Landau damping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…According to , possible sinks of ULF wave energy include at least three mechanisms: damping through ionospheric Joule heating, generalized Landau damping, and mode coupling. By comparing the effects of Landau damping, Joule heating, and waveguide propagation, Wang et al (2015) found that Joule heating and magnetospheric waveguide propagation are insufficient to account for the observed decay rate of ULF wave energy in this event. However, Landau damping of the wave due to driftbounce resonance with energetic ions was estimated to be higher than that provided by Joule heating (Fig.…”
Section: Growth and Damping Of Ulf Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to , possible sinks of ULF wave energy include at least three mechanisms: damping through ionospheric Joule heating, generalized Landau damping, and mode coupling. By comparing the effects of Landau damping, Joule heating, and waveguide propagation, Wang et al (2015) found that Joule heating and magnetospheric waveguide propagation are insufficient to account for the observed decay rate of ULF wave energy in this event. However, Landau damping of the wave due to driftbounce resonance with energetic ions was estimated to be higher than that provided by Joule heating (Fig.…”
Section: Growth and Damping Of Ulf Wavesmentioning
confidence: 99%
“…18). Wang et al (2015) estimated that drift-bounce resonance between ULF waves and O ? ions with energies ranging from a few keV to tens of keV is sufficient to explain the rapid wave damping rates observed by Cluster on Nov 7, 2004.…”
Section: Growth and Damping Of Ulf Wavesmentioning
confidence: 99%
“…If the majority of power is driven at the magnetopause, then this suggests that ULF waves have a long lifetime in the magnetosphere and can transit the enormous distance between the magnetopause and the 10.1029/2020JA028345 plasma torus at Io's orbit-in stark contrast with the terrestrial magnetosphere, where ULF waves have been observed to dissipate in tens of minutes (Wang et al, 2015). We can compare this to an estimate of how far fast-mode waves could penetrate into the magnetosphere over a Jovian rotation by assuming conservative ranges in the Alfvén and sound speed in the plasma sheet of 100-300 km/s (Bagenal et al, 2017;Kivelson, 2016).…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…At SSCs, fast‐mode magnetosonic waves launched by interplanetary shocks impinging on the magnetosphere can transfer to standing shear Alfvén waves through field line resonance (Kivelson & Southwood, ); similar excitation of global Pc5 Alfven waves has been seen even for less dramatic pressure drivers in the solar wind (Takahashi et al, ). Standing shear Alfvén waves in the ULF band can exchange their energy with charged particles efficiently through drift‐bounce resonance (Wang et al, ). Theoretical studies of drift‐bounce resonance were first carried out by Southwood and Kivelson () and evidenced by various observations (e.g., Chaston et al, ; Takahashi et al, ; Yang et al, , ).…”
Section: Introductionmentioning
confidence: 99%